2023
DOI: 10.2147/ijgm.s402671
|View full text |Cite
|
Sign up to set email alerts
|

Construction of circRNA–miRNA–mRNA Network Reveal Functional circRNAs and Key Genes in Acute Myeloid Leukemia

Abstract: Introduction:CircRNA is closely correlated with a wide variety of processes of acute myeloid leukemia (AML), whereas the novel circRNAs, their molecular mechanism and the specific function they played in AML should be explored in depth. Methods:The microarray chip data of AML patients and normal samples in the Gene Expression Omnibus (GEO) database were selected to differentially expressed (DE) circRNA, miRNA, and mRNA genes. The miRNA gene was the intersection of the circRNA target gene predicted using CSCD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…2 Furthermore, existing research has suggested that circRNAs are capable of playing a role in the post-transcriptional regulation of AML by binding miRNAs, activating downstream signaling cascades, and regulating the expression of related genes, closely correlated with a wide variety of processes of AML. 7 AML has a poor prognosis and a considerable tendency to relapse 1 therefore, the need for effective treatment is undeniable.…”
Section: Dear Editormentioning
confidence: 99%
“…2 Furthermore, existing research has suggested that circRNAs are capable of playing a role in the post-transcriptional regulation of AML by binding miRNAs, activating downstream signaling cascades, and regulating the expression of related genes, closely correlated with a wide variety of processes of AML. 7 AML has a poor prognosis and a considerable tendency to relapse 1 therefore, the need for effective treatment is undeniable.…”
Section: Dear Editormentioning
confidence: 99%
“…For example, in the bioinformatics study of Liu et al [ 5 ], it was emphasized that hsa_circRNA_0003638 may play a role in the pathogenesis of atrial fibrillation by targeting the CXCR4 gene via hsa-miR-1207-3p. Similarly, Hu et al [ 6 ] suggested that the interaction of hsa_circ_0009581 / hsa-miR-150-5p , and hsa_circ_0001947 / hsa-miR-454-3p may play a role in the AML cancer process. The precise biological classification of the BC subtype is critical for predicting the disease’s progression.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 With the development of bioinformatics and sequencing technologies, increasingly circRNAs are found and reported to play important roles in various biological activities. 20 An increasing amount of evidence shows that circRNAs play an important role in HCC occurrence and development.…”
Section: Introductionmentioning
confidence: 99%